KERJASAMA SMK NEGERI 1 SUMBERREJO DENGAN AHASS DAN TELKOM UNTUK MENINGKATKAN KOMPETENSI LULUSAN - Sriatun Sriatun; Ekohariadi Ekohariadi; Samani Samani; Umi Kulsum (Universitas Muhammadiyah Semarang, 2018)
Vocational education in State Vocational Schools in Bojonegoro, specially SMK Negeri 1Sumberrejo, is a replica of the environment where students work practices still need improvement like those in the industry today. Therefore the school tried to adjust these conditions, by conducting various collaborations, one of which was cooperation with Ahass and Telkom.The purpose of this study was to determine the characteristics of school collaboration with Telkom and Ahass and the mechanism of cooperation to improve the competence of vocational graduates, so that what is obtained in schools is link and match with the industry. Through a qualitative approach with descriptive methods, data collection techniques are carried out through interviews, observation, and documentation studies. The research subjects were DU / DI, headmaster, public relations officer, and productive teacher of TSM and TKJ at SMK Negeri 1 Sumberrejo. The results of the study found a vocational cooperation program, namely the preparation of a joint curriculum, apprenticeship of TSM to Ahass productive teachers in in-form, apprenticeship of TKJ productive teachers toTelkom in the form of fiber training, apprenticeship students both to ahass and to Telkom. The mechanism of collaboration between Vocational Schools and DU / DI is reflected in the agreement between the two parties in the form of MOU in the implementation of teacher apprenticeship, apprenticeship, competency testing, community service / free service with junior mechanical themes, hearings and seminar.Keywords: Kerjasama, Ahass dan Telkom, Kompetensi Lulusan.